Differences in visual search behavior between expert and novice team sports athletes: A systematic review with meta-analysis - Silva, Ana Filipa; Afonso, José; Sampaio, António; Pimenta, Nuno; Lima, Ricardo Franco; Castro, Henrique de Oliveira; Ramirez-Campillo, Rodrigo; Teoldo, Israel; Sarmento, Hugo; González Fernández, Francisco; Kaczmarek, Agnieszka; Oniszczuk, Anna; et al. (Frontiers in Psychology, 2022)
Background For a long time, in sports, researchers have tried to understand an expert by comparing them with novices, raising the doubts if the visual search characteristics distinguish experts from novices. Therefore, the aim of the present study was to review and conduct a meta-analysis to evaluate the differences in visual search behavior between experts and novices in team sports athletes. Methods This systematic review with meta-analysis followed the PRISMA 2020 and Cochrane's guidelines. Healthy team athletes were included, which engaged in regular practice, from any sex or competitive level, specifically classified a priori as expert or novice in the original research (i.e., if they were classified after the experiment, based on one of the tests, the study would be excluded). We considered only research published in peer-reviewed journals, with no limitations regarding date or language. It was considered healthy team sport athletes engaged in regular practice. The scenarios could be in situ or film-based. The databases of EBSCO (Academic Search Complete, Academic Search Ultimate, APA PsycArticles, and APA PsycINFO), PubMed, Scopus, SPORTDiscus, and Web of Science were used to perform the searches. The risk of bias was calculated through the RoBANS tool. Results From a total of 6,257 records, of which 985 were duplicates, titles and abstracts of 5,272 were screened, and 45 required full-text analysis. Of those, 23 were excluded due to not fulfilling the eligibility criteria regarding participants. In the end, 22 studies were selected, however, as two studies were part of the same trial and were analyzed conjointly. Discussion Experts showed to be older and with more years of practice. The ability to distinguish experts from novices was not so clear regarding the variables analyzed. This could be due to the strategies chosen in each study, which were specific to each scenario, and when grouping all together, it was lost information within non-representative averages. The distinction between experts and novices was not clear, showing a lot of heterogeneity in the included studies. The expert classification itself may have been the conditioning aspect for these results, retaining the doubt and the need for more studies in the field. Systematic review registration The protocol was pre-registered in OSF (project https://osf.io/3j4qv/, register https://osf.io/dvk2n).